Application of Berry’s Index in the Analysis of Bite Mark - Nur Qistina Binti Ahmad Fauzi; Gheena S (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: This study was done to evaluate the importance of applying Berry’s index in bite markanalysis.With that, it is able to highlight the usefulness of Berry’s index in aiding the analysis of bite markof an individual.Methods: The study was conducted among 60 students between the ages of 18-30 from Saveetha DentalCollege, Chennai. The data that was obtained was then tabulated and statistically analyzed.Conclusion: The results of the study revealed that the widths of both maxillary central incisors and thebizygomatic width were higher in males when compared to females. A positive correlation can be found inmales compared to females in regard to both of the widths obtained. Berry’s index is a useful tool of highforensic value and can be used to help in the identification of an individual’s facial proportions based on thecalculated width of the central incisors. Thus, it can be of correlation to that of forensic facial reconstruction.